The Study of Lipid Biomarkers and Contemporary Microbial Communities in Early-Eocene Sedimentary Records at Chicxulub Impact Crater - Wang, Danlei (Curtin University, 2021)
This thesis employed comprehensive analytical techniques, including organic geochemistry and molecular microbial ecology, to investigate sedimentary lipid biomarker records and contemporary microbial communities recovered from an early Eocene interval in the Chicxulub impact crater, Gulf of Mexico. This study provided 1) indirect evidence for the possibility of lipid biomarker biodegradation during refrigerated storage of sediment cores from the deep subsurface biosphere and 2) highly-resolved lipid biomarker evidence revealing orbital controls on paleoenvironmental and microbial communities during the end of the EECO.